Vision Mission of Muhammadiyah University in Indonesia: Ideology Analysis Of Norman Fairclough Approach - Kundharu Saddhono; Fabio Testy Ariance Loren; Luthfiatun Latifah (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2017)
Muhammadiyah have features to build the spirit of social and community educa- tion to be more developed and educated. showing the teachings of islam is not just a religion personal and static but dynamic and domiciled as a human life in all aspects. This study attempts to describe and explain the ideology of the vision and mission of Muhammadiyah University in Indonesia using content analysis method. This research is expected to descriptive qualitative research with the critical analysis discourse approach as suggested by Norman Fairclough with the elements that analyzes namely representation, relationships, and the identity. The results of the analysis element representation shows that almost all Muhammadiyah University in Indonesia has ideology Islam and Muhammadiyah to be ijtihad and tajdid based on and Muhammad ways. Direction and purpose from which missions made focused on Islamic values. While when viewed from the aspect most many appear on a mission is the aspect of religiously so further strengthen the statement. In addition to that is the nature of Muhammadiyah will influence in the formation of this mission, namely of active properties in the progression of society with a view islah and development in accordance with the teachings of Islam. Meaning which is formed on the series of between another sentences put the vision and mission in a positive representation so that it can affect those who read it. The relation of elements show that vision and mission Muhammadiyah University in Indonesia construed most only to proselyte Islamic. Elements power in it is so great that relation which is construed in a discourse vision is something that is regarded reasonable for the maker. While of an identity element that discourse maker displayed in the text is a personal, group, or institution that submitted to Islam.